Pluralisme Teoretis Dalam Kajian Kesehatan Respiratori Remaja Urban: Evaluasi Kritis Model Klasik Dan Kontemporer Menuju Sintesis Berbasis Kebutuhan Kesehatan Masyarakat - Mardiana, Eka; Fachri , Muhammad; Lusida , Nurmalia (Jurnal Ragam Pengabdian, 2026)
Urban adolescent respiratory health has emerged as a major public health concern due to the combined effects of air pollution, tobacco smoking, vaping, and climate change during a critical stage of lung development. Existing studies commonly apply theoretical frameworks in isolation, limiting a comprehensive understanding of the interactions among individual, social, environmental, and policy determinants. This systematic literature review aimed to evaluate the strengths and limitations of classical and contemporary theoretical models in explaining respiratory health among urban adolescents. A narrative systematic literature review was conducted following the PRISMA 2020 guidelines and the PECO framework. Articles published between 2020 and May 2026 were retrieved from Scopus and ScienceDirect, resulting in 60 eligible studies for synthesis. Classical models, including the Health Belief Model, Theory of Planned Behavior, and Social Cognitive Theory, effectively explained voluntary health behaviors, such as smoking, vaping, vaccination, and mask use, but were less capable of addressing involuntary environmental exposures. In contrast, socio-ecological and contemporary frameworks, including Planetary Health, Eco-social Theory, the Exposome, and Syndemic Theory, provided a more comprehensive perspective by integrating social inequalities, environmental exposures, and biological mechanisms. The findings highlight the importance of structured theoretical pluralism to support evidence-based, multilevel public health interventions for improving urban adolescent respiratory health, particularly in low- and middle-income countries such as Indonesia.